REPRESENTASI SISWA KELAS XI SMKN 2 PALU DALAM MEMECAHKAN MASALAH FUNGSI KUADRAT: Representation Of Students Of Class Xi Smkn 2 Palu In Solving Quadratifical Function Problems - Firnasari; Rizal, Muh. (Universitas Tadulako, 2024)
This study aims to obtain a description of the representation of students with high, medium, and low mathematical abilities in solving quadratic function problems. The subjects of this study were three class XI students of SMKN 2 Palu in the even semester of the 2019/2020 school year. Three students selected as research subjects consisted of a student with high math ability, a student with moderate math ability, and a student with low math ability. Data representation of the three subjects was obtained through problem solving tests and unstructured interviews which were then analyzed qualitatively. The results of this study indicate that students with high mathematical abilities use a combination of verbal representations, visual representations and symbolic representations in solving a given quadratic function problem.While students with moderate math ability and students with low math abilities use verbal representations and symbolic representations in solving the quadratic function problem given. Although the two students use the same representation but in different ways, and students with moderate mathematical abilities use more symbolic representations, while students with low math abilities use more verbal representations.